The value of testicular ultrasound in the prediction of the type and size of testicular tumors - Abraham Shtricker; David Silver; Elias Sorin; Letizia Schreiber; Nachum Katlowitz; Alexander Tsivian; Kalman Katlowitz; Shalva Benjamin; Abraham Ami Sidi (International Brazilian Journal of Urology, 2015)
ABSTRACTObjectives:Ultrasound (US) is often used for the work-up of testicular pathology. The findings may implicate on its management. However, there is only scant data on the correlation between US findings and testicular tumor type and size. Herein, we report on a multicenter study, analyzing these correlations.Methods:The study included patients who underwent orchiectomy between 2000 and 2010. Their charts were reviewed for US echogeneity, lesion size, pathological dimensions, histology, and the presence of calcifications, fibrosis, necrosis and/or intraepithelial neoplasia. The incidence of these parameters in benign versus malignant lesions and seminomatous germ cell tumors (SGCT) versus nonseminomatous germ cell tumors (NSGCT) was statistically compared.Results:Eighty five patients fulfilled the inclusion criteria, 71 malignant (43 SGCT, 28 NSGCT) and 14 benign. Sonographic lesions were at least 20% smaller than the pathologically determined dimensions in 21 (25%) patients. The ability of US in estimating the size of malignant tumors was 71%, compared to 100% of benign tumors (p=0.03), with no significant difference between SGCT and NSGCT. Necrosis was more frequent in malignant tumors (p=0.03); hypoechogeneity and fibrosis were more frequent in SGCT than in NSGCT (p=0.002 and 0.04 respectively).Conclusions:Testis US of malignant lesions underestimates the size in 25% of the cases, a fact that may impact on the decision of testicular sparing surgery. The ultrasonic lesions were eventually proven to be benign in 16% of the cases. Therefore it is advised to apply frozen sections in borderline cases. Hypoechogeneity is more frequent in SGCT than NSGCT.